2019
DOI: 10.1007/s10886-019-01074-4
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics of Thrips Resistance in Pepper (Capsicum spp.) Reveals Monomer and Dimer Acyclic Diterpene Glycosides as Potential Chemical Defenses

Abstract: The development of pesticide resistance in insects and recent bans on pesticides call for the identification of natural sources of resistance in crops. Here, we used natural variation in pepper ( Capsicum spp.) resistance combined with an untargeted metabolomics approach to detect secondary metabolites related to thrips ( Frankliniella occidentalis ) resistance. Using leaf disc choice assays, we tested 11 Capsicum accessions of C.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 61 publications
1
46
1
2
Order By: Relevance
“…The classification of relative thrips resistance or susceptibility of the accessions was based on the leaf disc choice assays (Table 1 , Macel et al 2019 ). This resistance classification was compared with resistance in whole plant thrips performance assays and in no-choice leaf discs feeding damage assays (Visschers et al 2019a ) (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The classification of relative thrips resistance or susceptibility of the accessions was based on the leaf disc choice assays (Table 1 , Macel et al 2019 ). This resistance classification was compared with resistance in whole plant thrips performance assays and in no-choice leaf discs feeding damage assays (Visschers et al 2019a ) (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Recent bans on pesticides and increasing resistance to the insecticides that are still used call for identifying natural sources of resistance in crops. Plant metabolites linked to thrips resistance are amongst others alkaloids (Liu et al 2019 ), chlorogenic acid (Leiss et al 2009 ), tocopherols (Maharijaya et al 2012 ) and diterpene glycosides (Macel et al 2019 ; Maharijaya et al 2018 ). However, in most studies the entire leaf was analyzed and not specifically the wax compounds.…”
Section: Introductionmentioning
confidence: 99%
“…F I G U R E 1 Schematic overview of previous studies conducted on resistance to thrips in Capsicum (Macel et al, 2019;Visschers et al, 2019) that formed the foundation of the experiments reported here (displayed in bold)…”
Section: Sitementioning
confidence: 99%
“…Previously, we screened 40 Capsicum accessions for resistance to two thrips species using leaf disc assays . This resulted in the identification of 11 accessions that were either relatively resistant or susceptible to F. occidentalis (Macel et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Diterpene glycosides (DTGs) are a diverse compound class whose members are often associated with phytotoxic activities (Macias et al, 2008) and have potent antiherbivore resistance/deterrence effects. For example, the abundance of monomers and dimers of capsianosides is correlated with thrips resistance in pepper (Macel et al, 2019) and 17-hydroxygeranyllinalool diterpene glycosides (HGL-DTGs) in Nicotiana species have been shown to function in resistance against larvae of the specialist herbivore Manduca sexta (Lou and Baldwin, 2003;Jassbi et al, 2008;Heiling et al, 2010) and the generalist herbivore, Heliothis virescens (Snook et al, 1997).…”
Section: Introductionmentioning
confidence: 99%